ANALISIS KESALAHAN MAHASISWA DALAM GEOMETRI DENGAN KRITERIA ENNIS - Kristiani, Kristiani; Nisa, Sitta Khoirin; Irsyadi, Khafid; Yunani, Fitria (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
The aim of this research is to describe student errors in geometry using Ennis criteria. This research uses a qualitative approach and descriptive research type. Research instruments include tests, interviews. This research took 3 subjects with different abilities, namely students with high abilities, students with medium abilities and students with low abilities. Based on the research results, it was concluded that students' mistakes in solving problems based on Ennis' criteria were that students with high abilities made mistakes in the overview section. And students with moderate abilities make mistakes in the criteria of focus, inference, situation, clarity and overview. Wherease, students with low mathematical skills make mistakes in the criteria of focus, reason, situation, clarity and overview.